PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP LOYALITAS DI MEDIASI OLEH KEPUASAN PELANGGAN PADA PELANGGAN JNE DI KOTA BANDA ACEH - Adam Albani; Hafasnuddin Hafasnuddin (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to see the effects of customer satisfaction related to service quality, price and loyalty to JNE customers in the city of Banda Aceh. Therefore this study provides literature on the contribution to service quality, price and loyalty through its mediating role on customer satisfaction. The sampling technique used is non-probability sampling with purposive sampling method. The data were analyzed through the Statistical Package Social Science (SPSS) program which was then tested for validity and reliability tests so that the data that had been collected was not biased. Hypothesis testing was carried out using the Hierarchial Linear Modeling (HLM) method to determine the effect between variables. The results of hypothesis testing were carried out partially (t test) to determine the direct effect between variables and using the Causal Step method to determine the indirect effect between variables. Based on the results of the analysis, service quality and price have a positive and significant effect on customer satisfaction. In addition, customer satisfaction has a positive and significant effect on loyalty. In this relationship, customer satisfaction has an effect as a mediating relationship between quality and price with loyalty